2020
DOI: 10.21203/rs.2.21834/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of High Fertility Rate among Married Women in Ethiopia

Abstract: Background: Fertility is one the major components of changing the population size and structure over time. Hence, this study aims to identify the socioeconomic and demographic factors associated with the high fertility rate among married women in Ethiopia Method: Ethiopian demography and health survey of 2016 data were accessed and used for the analysis. A total of 9602 married women were included in the study. Poisson regression models were employed by considering the number of children ever born (count) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…However, in this study, the level of education was not found to be statistically significant in predicting the effect of the number of children ever born. This finding was in line with prior studies (Adhikari, 2010;Azmoude et al, 2017) but in contrast with studies (Aragaw et al, 2023;Atsbaha et al, 2016;Mekonnen & Worku, 2011b;Muche & Gebremichael, 2020;Rutaremwa et al, 2015). Although educated women are usually more aware of family planning methods and the advantages and disadvantages of having children, they should have more autonomy and power in making reproductive decisions, so that they experience a lower fertility rate.…”
Section: Discussionsupporting
confidence: 89%
“…However, in this study, the level of education was not found to be statistically significant in predicting the effect of the number of children ever born. This finding was in line with prior studies (Adhikari, 2010;Azmoude et al, 2017) but in contrast with studies (Aragaw et al, 2023;Atsbaha et al, 2016;Mekonnen & Worku, 2011b;Muche & Gebremichael, 2020;Rutaremwa et al, 2015). Although educated women are usually more aware of family planning methods and the advantages and disadvantages of having children, they should have more autonomy and power in making reproductive decisions, so that they experience a lower fertility rate.…”
Section: Discussionsupporting
confidence: 89%
“…Other factors being equal, the difference in the rate of children ever born for contraceptive users is 0.641 times lower than for non-users. This finding was consistent with some studies [48,56,57,60,63] but in contrast with [55,58]. The rationale behind the decline in fertility rates can be attributed to the crucial role played by contraception in promoting healthy timing and spacing of pregnancies.…”
Section: Declarationsupporting
confidence: 92%
“…However, in this study, the level of education was not found to be statistically significant in predicting the number of children ever born. This finding was in line with prior studies [56,59] but in contrast with studies [49,55,57,60,61]. Although educated women are usually more aware of family planning methods and the advantages and disadvantages of having children, they should have more autonomy and power in making reproductive decisions, so that they experience a lower fertility rate.…”
Section: Notesupporting
confidence: 90%
See 2 more Smart Citations